434 AUTOLOGOUS HEMATOPOIETIC CELL TRANSPLANTATION FOR CHRONIC LYMPHOCYTIC LEUKEMIA AND SMALL LYMPHOCYTIC LYMPHOMA: THE SEATTLE EXPERIENCE. (1st January 2006) - Dau, Q.; Gopal, A. K.; Gooley, T.; Pagel, J. M.
Abstract : Although conventional chemotherapeutic treatment regimens have not been shown to be curative for patients with chronic lymphocytic leukemia (CLL) and small lymphocytic leukemia (SLL), treatment with regimens employing agents such as fludarabine or chlorambucil are typically instituted when patients become symptomatic. Fludarabine-containing regimens yield high overall response rates and, in some cases, longer complete remissions (CR). However, many patients relapse and become fludarabine refractory, with a median survival of ≤ 1 year. For some of these patients, autologous hematopoietic cell transplantation (HCT) with myeloablative conditioning has been employed as a therapeutic option with curative potential. Using a retrospective analysis of electronic charts we have reviewed our experience treating CLL/SLL patients with autologous HCT to gain further insight into the potential efficacy of this approach. From 1992 to 2004, 24 patients with CLL ( n = 10) or SLL ( n = 14) were treated with autologous HCT in Seattle. Three-year OS and relapse rates are estimated to be 33% and 30%, respectively. Non-relapse mortality (NRM) at 100 days and 3 years are estimated to be 25% and 42%, respectively. These data suggest that high-dose chemotherapy and/or radiation therapy followed by autologous HCT can induce long-term remissions for patients with CLL/SLL; however, this procedure is associated with a high rate of relapse and NRM post-transplant. Novel methods to reduce relapse and NRM, thereby improving OS, are required for selected patients considered candidates for autologous HCT in the future.